New Economic Statecraft : China, the United States and the European Union. - Xiaotong, Zhang (Taylor & Francis, 2024)
This book provides insights on the art of governing a state and managing its external relations from a wealth-power logic. It looks at ""economic statecraft"", which consists of wealth production, wealth mobilization, and wealth-power conversion by a state.